2019
DOI: 10.15407/mfint.41.06.0817
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the Aging Time on Microstructure and Mechanical Properties of the AA7075 Alloy after T6 Heat Treatment

Abstract: In this study, the effect of the aging time on microstructure and mechanical properties of the AA7075 alloy after T6 heat treatment is investigated. The AA7075 alloys are quenched after solid solution treatment at 485°C for 2 hours and artificially aged at 120°C using five different aging times. Hardness measurements, microstructure examinations (SEM + EDS, XRD), and tensile tests are performed for the aged alloys. Fractured surfaces are also examined using SEM images after the tensile testing. The results of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Similarly, these tiny precipitates were crucial for the formation, growth, and coalescence of microvoids. Particularly, during the process of hot plastic deformation, the refined and hard precipitated phases were easily regarded as sites for void nucleation, which promoted the formation of microvoids, as has been confirmed by Simsek et al [ 35 ]. Then, the nucleation and growth of microvoids subjected to external loads accelerated the generation and deterioration of microcracks, as can be observed in Figure 9 .…”
Section: Drx Characterization and Precipitate Evolutionmentioning
confidence: 69%
See 1 more Smart Citation
“…Similarly, these tiny precipitates were crucial for the formation, growth, and coalescence of microvoids. Particularly, during the process of hot plastic deformation, the refined and hard precipitated phases were easily regarded as sites for void nucleation, which promoted the formation of microvoids, as has been confirmed by Simsek et al [ 35 ]. Then, the nucleation and growth of microvoids subjected to external loads accelerated the generation and deterioration of microcracks, as can be observed in Figure 9 .…”
Section: Drx Characterization and Precipitate Evolutionmentioning
confidence: 69%
“…Consequently, it should be noted that precipitate-induced damage also plays a comprehensive role. Simsek et al [ 35 ] believed that the fine and hard precipitated phases are easily used as the location of void nucleation, thus promoting the formation of microvoids. From the fracture morphology in Figure 10 a,b, there are precipitated phases with inclusions in the dimples [ 43 , 44 ].…”
Section: Multiscale Modelling Of Viscoplastic Behaviormentioning
confidence: 99%
“…Aging heat treatment is commonly used for hardening aluminum alloys and improving their mechanical strength [2]. The hardness and strength of these alloys are increased by secondary phase precipitates formed in the microstructure and by obstructing/preventing the dislocation movement of these precipitates with the aging heat treatment [3,4]. The aging heat treatment is carried out in three stages.…”
Section: Introductionmentioning
confidence: 99%
“…The authors reported that an increase in the temperature of solution enabled the formation of secondary phase solutions, which led to an increase in hardness and strength. Şimşek et al [3] studied the effects of T6 heat treatment applied for different aging times on the microstructure and mechanical properties of AA7075 alloys. The researchers aged the alloys between 15 hours and 35 hours, observed that the samples that were aged for 25 hours showed the highest hardness and tensile strength values, and reported that the hardness and tensile strength decreased when the alloys were aged further.…”
Section: Introductionmentioning
confidence: 99%